# How do you simplify #(6qr^3)/(-2q^5r)#?

You can write numbers,

By signing up, you agree to our Terms of Service and Privacy Policy

To simplify (6qr^3)/(-2q^5r), you divide each term in the numerator by the corresponding term in the denominator:

(6qr^3)/(-2q^5r) = (6/(-2)) * (q/q^5) * (r^3/r)

= -3 * q^(1-5) * r^(3-1)

= -3 * q^(-4) * r^2

= -3r^2/q^4

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7